Early Post-Stroke Electroacupuncture Promotes Motor Function Recovery in Post-Ischemic Rats by Increasing the Blood and Brain Irisin - Liu, Li (Neuropsychiatr Dis Treat, 2021)
OBJECTIVE: Recent studies have shown that irisin, a novel peptide hormone derived from muscles, could be used as a potential therapeutic drug against ischemic stroke. Moreover, electroacupuncture (EA) is widely used in the treatment of ischemic stroke. Yet, whether irisin is involved in the EA neuroprotection remains unclear. The following study investigated the association between serum and peri-lesional cortex irisin and EA-induced post-stroke motor recovery in rats. METHODS: The middle cerebral artery occlusion (MCAO) method was used to induce ischemic stroke in rats. Rats were randomly divided into two groups: a middle cerebral artery occlusion (MCAO) group (MCAO rats without treatment) and an electroacupuncture (EA) group (MCAO rats treated with EA). On the 3rd day post-stroke, infarct volume, behavioral deﬁcits, surviving neurons, irisin protein expression in peri-infarction cortex, muscle tissue, and serum were evaluated to identify the neuroprotective of EA in acute ischemic stroke. RESULTS: Compared with the MCAO group, the EA group showed better behavioral performance, a smaller cerebral infarct volume, more surviving neurons, and a significant increase in irisin expression in the peri-infarction cortex and serum (p<0.05). However, no difference in irisin expression in the muscle tissue was found between the MCAO group and the EA group (p>0.05). CONCLUSION: EA promotes motor function recovery, reduces the volume of cerebral infarction, and alleviates neuronal death following ischemic stroke by enhancing the expression of irisin in both the blood and peri-lesional cortex.